PEMANFAATAN ENTOMOPATOGEN INDIGENOUS INDONESIA SEBAGAI KANDIDAT BIOPESTISIDA RAMAH LINGKUNGAN TERHADAP HAMA PENTING TANAMAN CABAI - Salaki, Ch L; Pelealu, Jantje (EUGENIA, 2018)
The purpose of this study was to obtain potential isolates of entomopathogenic bacteria and fungi that can be formulated into superior biopesticide candidates. The research methods used were 1) exploration of entomopathogenic bacteria and fungi from isolation of soil samples and infected insect pests, 2) rearing test insects and chili plant nurseries, 3) testing the killing power of entomopathogenic bacterial and fungal isolates against key pests of chilli plants and 4) pathogenicity testing of entomopathogenic bacteria and fungi to chilli plant pests. 104 soil samples were obtained from the field, consisting of paddy soil, plantation land, yard and forest soil with 21 isolates of Bacillus thuringiensis isolates. Sampling of entomopathogenic fungi was found in 17 insects attacked by entomopathogenic fungi. From the results of testing of all B. thuringiensis isolates, there were 12 isolates that could kill test larvae (S. litura) at a success rate greater than 50% 96 hours after preparation and 8 isolates that were able to kill the test nymph (M. persicae) at a success rate greater than 50% 96 hours after treatment. The results of testing the killing power of entomopathogenic fungi isolates were found to be the highest ability to kill S. litura larvae (93.3%), followed by MMITO isolates (86.7%) and MMSAM (80.0%). These isolates were isolates from the fungus Metarhizium anisopliae. The results of the selection of B. bassiana isolates in S. litura larvae were the best isolates of BEMSAM (86.7%) followed by BEMTTO isolates (83.3%). Whereas for testing the nymph Myzus persicae, mortality above 50% occurred through 2 isolates of Metarhizium anisopliae and 3 isolates of Beauveria bassiana. The pathogenicity test of Bacillus thuringiensis isolates showed that the highest mortality of Spodoptera litura in TTM isolates with a concentration of 5.02 x 105 with the fastest death time 28.2 hours after treatment. Whereas in the test of Myzus persicae, the highest mortality was in the TYM isolate with a concentration of 6.3 x 104 with the fastest death time was 22.4 hours after treatment.